2021
DOI: 10.3390/insects12050424
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Wound!—Fruit Injury Ranks Higher than, and Interacts with, Heterospecific Cues for Drosophila suzukii Oviposition

Abstract: Drosophila suzukii is a globally distributed insect that infests many economically important fruit varieties by ovipositing into ripening fruits. The mechanisms underlying host selection, in particular the fly’s preference for fresh, intact, and competitor-free fruits, are only partially understood. We hypothesize that D. suzukii females use cues of different fruit properties to rank potential host fruits in a hierarchical manner. We created four naturally occurring fruit (blueberries) categories: (1) intact; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Cornmeal media was used as the egg laying substrate in this study. Similar observations were made when fruits were used as the egg laying substrate, where D. suzukii laid fewer eggs on blueberry fruits previously visited and defecated on by D. melanogaster [ 37 ]. Whilst here we exposed the cornmeal media to D. melanogaster for 48 h, Kienzle and Rohlfs [ 37 ] only exposed blueberry fruits to D. melanogaster for 1.5 h, during which time they observed that D. melanogaster visited and defecated on the fruits but did not lay eggs.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Cornmeal media was used as the egg laying substrate in this study. Similar observations were made when fruits were used as the egg laying substrate, where D. suzukii laid fewer eggs on blueberry fruits previously visited and defecated on by D. melanogaster [ 37 ]. Whilst here we exposed the cornmeal media to D. melanogaster for 48 h, Kienzle and Rohlfs [ 37 ] only exposed blueberry fruits to D. melanogaster for 1.5 h, during which time they observed that D. melanogaster visited and defecated on the fruits but did not lay eggs.…”
Section: Discussionsupporting
confidence: 55%
“…Similar observations were made when fruits were used as the egg laying substrate, where D. suzukii laid fewer eggs on blueberry fruits previously visited and defecated on by D. melanogaster [ 37 ]. Whilst here we exposed the cornmeal media to D. melanogaster for 48 h, Kienzle and Rohlfs [ 37 ] only exposed blueberry fruits to D. melanogaster for 1.5 h, during which time they observed that D. melanogaster visited and defecated on the fruits but did not lay eggs. Further studies using wild-caught D. suzukii and fruit instead of cornmeal media and conducted in horticultural settings such as in glasshouses or polytunnels are planned but these are beyond the scope of this initial study.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations